1995
DOI: 10.1104/pp.107.3.857
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Nodule-Specific Polysaccharide Produced by Bradyrhizobium japonicum Bacteroids

Abstract: A polysaccharide produced by 5radyrhizobium japonicum bacteroids i n nodules (NPS) on soybean (Glycine max [LI Merr.) roots is different in composition and structure from the extracellular polysaccharide produced in culture by this organism. lsogenic strains either capable or incapable of NPS synthesis supported similar rates of plant growth and nitrogenase activity, indicating that polysaccharide deposition was not detrimental. The possibility that NPS may have some protective or nutritional role for bacteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…(1993) reported no significant decline in soybean rhizobia for up to 4 years after the last crop. It has been suggested that such ability to survive over long periods of time in soil might be helped to some degree by the protective action of a nodule-specific polysaccharide (Streeter et al, 1995) though these substances appear unlikely to persist for long periods of time in soil.…”
Section: Influence Of the Legume Host On Rhizobial Populations Anmentioning
confidence: 98%
“…(1993) reported no significant decline in soybean rhizobia for up to 4 years after the last crop. It has been suggested that such ability to survive over long periods of time in soil might be helped to some degree by the protective action of a nodule-specific polysaccharide (Streeter et al, 1995) though these substances appear unlikely to persist for long periods of time in soil.…”
Section: Influence Of the Legume Host On Rhizobial Populations Anmentioning
confidence: 98%
“…Six soybean seeds, cv Flint, were planted and each seed was irrigated with a fresh culture of B. japonicum. The wild-type strain was USDA 438 (NPS + ) and the NPS-strain was a transposon insertion mutant of 438 (Streeter et al . 1995).…”
Section: Plant Growthmentioning
confidence: 99%
“…1992). It is certain that the nodule‐specific polysaccharide (NPS) is a bacterial product, not a plant product, and that bacteroids are unable to hydrolyse NPS after they synthesize it (Streeter et al . 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of low N 2 -fixing and ineffective rhizobia cheating strains in the same plant is common (Singleton and Tavares, 1986;Bronstein, 2001), and accumulation of resources by some non-fixing rhizobia in bacteroid stage has been proposed as cheating advantage at plant´s expenses (Denison, 2000). However, this accumulation is a general metabolic consequence of reduced carbon demand from the plant (Lodwig, 2003) and not necessarily implies rhizobia further survival advantages (Streeter et al, 1995).…”
Section: Introductionmentioning
confidence: 99%